The SAGES Manual of Robotic Surgery (Springer International Publishing, 2018)
The SAGES Manual of Robotic Surgery is designed to present a comprehensive approach to various applications of surgical techniques and procedures currently performed with the robotic surgical platform. The Manual also aligns with the new SAGES UNIVERSITY MASTERS Program. The Manual supplements the Robotic Surgery Pathway from Competency to Proficiency to Mastery. Whether it's for Biliary, Hernia, Colon, Foregut or Bariatric, the key technical steps for the anchoring robotic procedures are highlighted in detail as well as what the reader needs to know to successfully submit a video clip to the SAGES Facebook Channels for technical feedback. The initial chapters are dedicated to the anchoring procedures needed to successfully navigate through the Masters Program. Subsequent chapters then address preliminary issues faced by surgeons and staff, such as training and credentialing, as well as instrumentation and platforms commonly used for these procedures. Individual chapters will then focus on specific disease processes and the robotic applications for those procedures.